2009
DOI: 10.5194/aab-52-512-2009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of roasted cereals and soybean in feed mixtures on fattening and slaughter traits as well as blood composition in fattening lambs

Abstract: Abstract. The study examined the effect of raw and roasted cereals (corn, oat and barley) and soybean in diet on growth performance and blood parameters of lambs fattening. Totally 60 lambs after ablactation at average of 50 days, were tested and equally divided into three groups: an experimental I (E I), experimental II (E II) and a control (C) group. The fattening period lasted 56 days. Lambs of the C group were fed on mixture with crude forages, those from the E I on mixture with roasted cereals and lambs o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
1
3

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
0
1
3
Order By: Relevance
“…Blood glucose and urea N was increased with the lambs that were fed SBM. Other studies reported results in conflict with those of this study [24,25], as they found that blood urea and glucose were reduced in cattle and lambs that consumed diets supplemented with different types of soybeans. The current study finding might be attributed to the higher availability and digestibility of nutrients, which might have caused elevated serum sugar and urea levels.…”
Section: Discussioncontrasting
confidence: 98%
“…Blood glucose and urea N was increased with the lambs that were fed SBM. Other studies reported results in conflict with those of this study [24,25], as they found that blood urea and glucose were reduced in cattle and lambs that consumed diets supplemented with different types of soybeans. The current study finding might be attributed to the higher availability and digestibility of nutrients, which might have caused elevated serum sugar and urea levels.…”
Section: Discussioncontrasting
confidence: 98%
“…La dieta que contenía soya integral mostró menor concentración de nitrógeno en orina (3.84 g día −1 ), similar a la dieta con pasta de soya (4.37 g día −1 ), la cantidad de nitrógeno excretado mostró variabilidad entre los tratamientos, con diferencias de aproximadamente 150% (grano de soya respecto a soya integral). En los granos de oleaginosas los tratamientos térmicos pueden generar condiciones propicias para la absorción de nutrientes, estos procesos resultan en enlaces entre carbohidratos solubles y aminoácidos libres, por lo que disminuye la solubilidad de las proteínas y aumenta la proteína de sobrepaso a nivel ruminal, de esta forma más proteínas llegan con su estructura intacta hasta el intestino delgado (Rafiee-Yarandi et al 2016), lo que puede mejorar el crecimiento de los animales (Antunović et al 2009). También las ganancias diarias de peso fueron superiores para los tratamientos con soya termoprocesada y soya integral respecto a la dieta con pasta de soya (316.66 y 304.44 vs 173.23 g día −1 , respectivamente).…”
Section: Resultados Y Discusiónunclassified
“…De esta manera, los tratamientos con pasta de soya termoprocesada y soya integral fueron superiores para consumo de materia seca y ganancia diaria de peso. Los granos termoprocesados tienen una mejor digestibilidad, debido a que durante el proceso de extrusión los granos se humedecen, de esta manera los componentes de almidón se gelatinizan, así como también algunos componentes proteicos se ven afectados en la elasticidad de sus enlaces (Antunović et al 2009), con lo que se tiene un mayor aporte de nutrientes resultando una mejor eficiencia alimenticia.…”
Section: Resultados Y Discusiónunclassified
See 1 more Smart Citation